2019
DOI: 10.1002/lt.25493
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of a Risk‐Adapted Protocol for the Evaluation of Coronary Artery Disease in Liver Transplant Recipients

Abstract: The prevalence and management of coronary artery disease (CAD) in liver transplantation (LT) candidates are not well characterized. The aims of this study were to evaluate the impact on clinical outcomes of a specifically designed protocol for the management of asymptomatic CAD in LT candidates and to investigate noninvasive risk profiles for obstructive and nonobstructive CAD for 202 LT candidates. Those with high baseline cardiovascular risk (CVR; defined by the presence of classic CVR factors and/or decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…All patients who received elective LT underwent standardized preoperative assessment, including blood analysis, chest X‐ray, electrocardiogram (ECG), pulmonary functional testing, and cardiac ultrasonography. Direct coronary imaging via computed tomography (CT) scan or direct cardiac catheterization was also obtained according to the cardiovascular recipients’ risk factors …”
Section: Methodsmentioning
confidence: 99%
“…All patients who received elective LT underwent standardized preoperative assessment, including blood analysis, chest X‐ray, electrocardiogram (ECG), pulmonary functional testing, and cardiac ultrasonography. Direct coronary imaging via computed tomography (CT) scan or direct cardiac catheterization was also obtained according to the cardiovascular recipients’ risk factors …”
Section: Methodsmentioning
confidence: 99%
“…89,90 However, non-invasive functional testing has limited predictive value for obstructive coronary artery disease in patients with cirrhosis, in whom the sensitivity and specificity of dobutamine stress echocardiography are reduced. 91,92 Although coronary angiography is considered the gold standard, studies performed in LT candidates are not completely conclusive, 93,94 making it difficult to predict the real impact of pre-LT asymptomatic cardiovascular abnormalities on long-term outcomes. However, a recent study has shown that pretransplant coronary artery disease, when adequately treated, may not affect post-LT survival.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…[42][43][44] The recent development of an angiographic screening protocol for LT candidates with high baseline cardiovascular risk may be a step in the right direction but needs further validation in larger and more diverse population cohorts. 45 Performing coronary angiography in this patient population carries higher risk of procedural complications due to high incidence of clotting disorders and renal insufficiency. 41 In addition, percutaneous coronary intervention or coronary artery bypass grafting before LT has not been shown to impart cardiovascular survival benefit.…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…However, DSE does not accurately reflect the severity of obstructive CAD in liver transplant candidates and despite various advances in knowledge, no gold standard has yet been developed for cardiac evaluation in LT candidates 42‐44 . The recent development of an angiographic screening protocol for LT candidates with high baseline cardiovascular risk may be a step in the right direction but needs further validation in larger and more diverse population cohorts 45 . Performing coronary angiography in this patient population carries higher risk of procedural complications due to high incidence of clotting disorders and renal insufficiency 41 .…”
Section: Etiologymentioning
confidence: 99%